(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Today, retailers are increasingly making use of various in-store influencers for converting browsers to spenders. However, success depends on how the customers perceive these influencers. The phenomenon of purchasing has been studied in consumer research as well as for example in psychology and economics since the 1950s. This study attempted to investigate the relationship of various factors, with buying behaviour of consumers in the Organized Retail Sector of Lucknow City of Uttar Pradesh, India. This article empirically evaluates the perception of the customers towards various in-store stimuli that is merchandise, promotion, displays and ambience, across stores located in Lucknow.